If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 42 = x + 12 Reorder the terms: 42 + 7x = x + 12 Reorder the terms: 42 + 7x = 12 + x Solving 42 + 7x = 12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 42 + 7x + -1x = 12 + x + -1x Combine like terms: 7x + -1x = 6x 42 + 6x = 12 + x + -1x Combine like terms: x + -1x = 0 42 + 6x = 12 + 0 42 + 6x = 12 Add '-42' to each side of the equation. 42 + -42 + 6x = 12 + -42 Combine like terms: 42 + -42 = 0 0 + 6x = 12 + -42 6x = 12 + -42 Combine like terms: 12 + -42 = -30 6x = -30 Divide each side by '6'. x = -5 Simplifying x = -5
| 4x^2=9+41 | | 7e^4x-5=11 | | 7x+3x=44 | | -x+x-2=2 | | 10x+45=x+81 | | 7x+3x=72 | | 12-(n-3)= | | 7=2x+11 | | R+4=20 | | z+4.9=8.8 | | 7x+60=x-6 | | 45=-5(k+4) | | 2/5x-=1/5x-12 | | 2sin^2-3cos+1=0 | | 11a^2+2a-17=0 | | 5a+6a=-6+8a | | 360=(x+40)+(4x+70)+(2x+110) | | x+47=54 | | 4x^2-2-8w=-6x | | -14x+1=21 | | 360=(x+50)+(2x+80)+(4x+20) | | x^4-5x^3-2x^2-3x-9= | | 5y-(3y+8)=3-(7y-9) | | 5(x-1)=3(2-x)-5 | | x+52=61 | | 11v-2v=54 | | x+78=86 | | 90x^2-63xy+18x=0 | | 7=m/125 | | -3.5b-1.75c= | | 4X+20=25-x | | x-2(-2x+20)=20 |